2011
DOI: 10.1007/s12028-011-9562-3
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Influence of Sevoflurane Anesthesia on Neuronal Survival and Cognitive Outcome After Transient Forebrain Ischemia in Sprague-Dawley Rats

Abstract: Postischemic neuronal survival was increased with 1.8 MAC compared with 0.45 MAC sevoflurane. Therefore, experimental models of cerebral ischemia should account for neuroprotective effects of sevoflurane with increasing concentrations. To ensure minimal interference of sevoflurane on neuronal survival, a low inspired concentration should be used and fluctuations in the depth of anesthesia should be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
8
1
Order By: Relevance
“…The results of the current study are also different from those of the study by Lasarzik et al, 17 in which higher concentrations of sevoflurane were associated with a better histologic outcome as compared with lower concentrations. Their experimental protocol was different from ours in 2 main ways.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the current study are also different from those of the study by Lasarzik et al, 17 in which higher concentrations of sevoflurane were associated with a better histologic outcome as compared with lower concentrations. Their experimental protocol was different from ours in 2 main ways.…”
Section: Discussioncontrasting
confidence: 99%
“…This implies that the low rates of cell death in our study probably would not be in correlation with cognitive impairment. Lasarzik et al (2011) showed that sevoflurane in high doses (4%), similar to ours, are more neuroprotective in regards of cell death than low dose (1%) in an ischemia model. The rats receiving 4% had a median of 3222 viable cells in the CA1 region, also similar to our young rats, and they did not show neurocognitive dysfunction using object recognition test.…”
Section: Discussionsupporting
confidence: 86%
“…Most neurons will die as a consequence of secondary energy failure, which occurs 6 to 15 h after injury [4]. The magnitude of primary cell death is dependent on the severity and duration of ischaemia/hypoxia and could not be observed in the neocortex within the first 13 min [28]. In the present study, we found that an insignificant increase of s100ß could be observed after 90 min of reperfusion.…”
Section: Discussionmentioning
confidence: 46%
“…For example, the basal ganglia and the hippocampus are more susceptible to ischaemia [28]. The proposed protective effects of levosimendan might become visible after a longer observation period and may not be associated with reduced glutamate release [39].…”
Section: Discussionmentioning
confidence: 99%